Dark horse [videorecording (DVD)] - Karina, Anna, 1940-2019-; Brasse, Claude (Sony Pictures Home Entertainment, 2016)
Set in a former mining village in Wales, an inspirational true story of a group of friends from a working men's club who decide to take on the elite 'sport of kings' and breed themselves a racehorse.